New insights in cardiac structural changes in patients with Fabry's disease - Linhart, A; Palecek, T; Bultas, J; Ferguson, J J; Hrudová, J; Karetová, D; Zeman, J; Ledvinová, J; Poupetová, H; Elleder, M; Aschermann, M (American heart journal, 2000)
BACKGROUND: Fabry's disease is an X-linked recessive genetic deficiency of the enzyme alpha-galactosidase leading to the pathologic intracellular deposition of neutral glycosphingolipids. Although cardiac involvement is frequent, there is controversy regarding the character of the associated left ventricular (LV) changes and the severity of valvular involvement. METHODS: Clinical evaluation (disease severity scaling, laboratory tests, and echocardiography) was performed in 13 hemizygous men (mean age 39 +/- 10 years) and 17 heterozygous women (mean age 35 +/- 19 years). RESULTS: LV hypertrophy (LVH) was frequent in subjects older than 30 years, more often in men (61%) than in women (18%, P <.001). The degree of LVH was independently associated with age and the logarithm of alpha-galactosidase activity (r(2) = 0.70, P <.001). The predominant LV geometric patterns were concentric LVH and remodeling, both present in 11 subjects (36%). Three patients had an asymmetric septal hypertrophy mimicking hypertrophic cardiomyopathy. In most subjects with LVH, the systolic function was normal and severe diastolic dysfunction (restrictive pattern) was not noted. Minor structural abnormalities of the mitral valve were found in 17 subjects (57%). The aortic valve was affected in 14 patients (47%). Valvular abnormalities were frequently accompanied by regurgitation of minor to mild degree. The presence of LVH or valvular changes was associated with increased disease severity. CONCLUSIONS: Echocardiographically detectable cardiac involvement is frequent with Fabry's disease, particularly in older subjects, and more pronounced in affected hemizygous men than in heterozygous women. LVH is frequently observed but usually not associated with significant systolic or restrictive diastolic dysfunction. Concentric LVH and remodeling appear to be the major manifestations of LV structural alteration. The frequently noted valvular abnormalities were not associated with a significant degree of regurgitation. Valvular and especially LV structural changes may serve as a useful marker of disease severity.
Keywords: Male; Biomarkers; Heart Valves; lidé středního věku; retrospektivní studie; diferenciální diagnóza; alfa-galaktosidasa; genotyp; stupeň závažnosti nemoci; kontrakce myokardu; Humans; glykosfingolipidy; Diagnosis, Differential; Middle Aged; biologické markery; alpha-Galactosidase; mužské pohlaví; Female; mladiství; Electrocardiography; Glycosphingolipids; ženské pohlaví; pohlavní dimorfismus; srdeční komory; srdeční chlopně; Fabry Disease; Retrospective Studies; Sex Characteristics; echokardiografie; Severity of Illness Index; Adult; Ventricular Dysfunction, Left; elektrokardiografie; biopsie; Echocardiography; Biopsy; Myocardial Contraction; Adolescent; dospělí; lidé; dysfunkce levé srdeční komory; Genotype; Fabryho nemoc; Heart Ventricles